Product Diversification, Adaptive Management, and Climate Change: Farming and Family in the U.S. Corn Belt - Valliant, Julia C. D.; Bruce, Analena B.; Houser, Matthew; Dickinson, Stephanie L.; Farmer, James R. (Frontiers in Climate, 2021)
A variety of factors shape farmers’ views as they face the rising effects of climate change and consider a range of adaptation strategies to build the resilience of their farming systems. We examine a set of related questions to explore farmers’ perspectives on risks and potential shifts to their operations: (1) Relative to other environmental factors, how salient of a challenge is climate change and climate-related impacts to farmers? (2) Do farmers intend to adapt to climate impacts generally? and (3) What factors shape their use of a specific and underexplored adaptive response—farm product diversification? The data come from a survey of 179 operators within a 30-county region of Indiana, Michigan, and Ohio. The region spans various rural-urban gradients. Respondents generally represent smaller operations (median of 80 acres (32 hectares)). Because our selection methods aimed to over-sample from food-producing farms, 60% of respondents produced some type of food or value-added product, and 40% produced only commodity feedstocks and biofuels. Although the group as a whole indicated only “somewhat” of a concern about changing weather patterns, and half did not anticipate adapting their farming practices to climate change, farmers’ responses to a write-in question denoted regional climate effects as challenges to their farms. Analysis of subgroups among the respondents, according to their views of climate change, adaptation, and further diversifying their agricultural products, distinguished farmers’ family considerations and gender. Methods to elicit subgroups included correlation, regression, cluster analysis and an examination of the many respondents (29%) who indicated uncertainty about adapting practices. Women, who participated in 29% of responses, indicated more concern with changing weather patterns and more openness to adapting farming practices compared to men. Farmers with the most family relationships to consider, and those with the greatest aspirations to employ descendants, were the most receptive to adapting their farming practices. This was the case even when respondents’ concern over climate change was low. Results point to the importance of family relationships as a factor in farmers' openness to implementing adaptive and potentially mitigative actions.